Homemade infant formula recipes may contain harmful ingredients: a quantitative content analysis of blogs. Issue 8 (11th June 2020) - Davis, Sutton A; Knol, Linda L; Crowe-White, Kristi M; Turner, Lori W; McKinley, Erin
Abstract: Objective: When breast-feeding is not possible, commercially made human milk substitute is recommended. Some consumers would prefer to make their own homemade infant formula (HIF) and may seek information on this practice from internet sources. The purpose of the current study was to investigate the content of blogs posting HIF recipes. Design: Blog postings were identified through a comprehensive search conducted using the Google search engine and the following search terms along with the term 'blog': 'Make Your Own Baby Formula', 'Homemade Baby Formula', 'Do It Yourself (DIY) Baby Formula', 'DIY Baby Formula', 'Baby Formula Recipe' and 'All Natural Baby Formula'. A quantitative content analysis of blogs offering recipes for HIF was completed. Blogs that met the inclusion criteria were reviewed for disclaimers, blogger's credentials, rationale for HIF use, advertisement or sale of recipe ingredients and recipe ingredients. Setting: Worldwide Web. Results: Fifty-nine blogs, featuring one hundred forty-four recipes, met inclusion criteria. Among reviewed blogs, 33·9 % did not provide a disclaimer stating breast milk is the preferred option, 25·4 % recommended consulting a healthcare professional before using, and 76·3 % and 20·3 % either advertised or sold ingredients or recipe kits, respectively. Credentials of bloggers varied and only seven bloggers identified themselves as 'nutritionists'. The three most frequently mentioned recipe ingredients were whole raw cow's milk (24·3 %), raw goat's milk (23·6 %) and liver (14·5 %). Conclusions: Clinicians should be aware of this trend, discuss source of formula with parents, advocate for appropriate infant feeding practices and monitor for side effects.